Watching the world change the stories behind the images of 9/11 - Friend, David 1955- (Farrar, Straus and Giroux, 2006)
Tells the stories behind the photographs of 9/11, discusses the controversy over whether the images are exploitative or redemptive, and shows how photographs help us witness, grieve, and understand the unimaginable.